Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
b = 0 and b = 4
Step-by-step explanation:
[tex]\frac{5}{3b^3-2b^2-5}[/tex] = [tex]\frac{2}{b^3-2}[/tex] ( cross- multiply )
2(3b³ - 2b² - 5) = 5(b³ - 2) ← distribute parenthesis on both sides
6b³ - 4b² - 10 = 5b³ - 10 ( subtract 5b³ from both sides )
b³ - 4b² - 10 = - 10 ( add 10 to both sides )
b³ - 4b² = 0 ← factor out b² from each term on the left side
b²(b - 4) = 0
equate each factor to zero and solve for b
b² = 0 ⇒ b = 0
b - 4 = 0 ⇒ b = 4
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.